Adhesive tape

An adhesive tape with a crosslinked (meth)acrylic copolymer, crosslinking agent, and tackifying resin addresses the challenge of low molecular weight adhesives, achieving improved processability and retention performance with reduced solvent use and enhanced adhesiveness.

JP2024177339AActive Publication Date: 2024-12-19SEKISUI CHEMICAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024173332
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-09-21
Filing Date
2024-10-02
Publication Date
2024-12-19
Estimated Expiration
2043-09-20

AI Technical Summary

Technical Problem

The challenge is to develop an adhesive tape with excellent retention performance and adhesiveness while using a (meth)acrylic copolymer with low molecular weight, which is necessary to reduce solvent content to mitigate CO2 emissions, without compromising bulk cohesive force, heat resistance, and adhesiveness.

Method used

The adhesive tape incorporates a crosslinked product containing a (meth)acrylic copolymer, a crosslinking agent, and a tackifying resin, with specific molecular weight ranges and gel fractions to achieve the desired properties.

Benefits of technology

The solution results in an adhesive tape with improved processability, reduced solvent use, and enhanced retention and adhesiveness, even with low molecular weight (meth)acrylic copolymers, maintaining bulk cohesive force and heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024177339000006
    Figure 2024177339000006
  • Figure 2024177339000007
    Figure 2024177339000007
  • Figure 2024177339000001
    Figure 2024177339000001
Patent Text Reader

Abstract

To provide an adhesive tape which has an adhesive layer having excellent retention performance and adhesiveness while using a (meth)acrylic copolymer having a low molecular weight.SOLUTION: There is provided an adhesive tape having an adhesive layer, wherein the adhesive layer contains a crosslinked product of an adhesive comprising a (meth)acrylic copolymer, a crosslinking agent and an adhesion-imparting resin, the weight average molecular weight of the (meth)acrylic copolymer in the region of a molecular weight of 5000 or more is 80000 and less than 500000 when the (meth)acrylic copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product is subjected to GPC measurement by differential refractometer RI detection, the adhesive tape bonded to an SUS plate does not fall off in a retention test which applies a 1 kg load for 24 hours in the shear direction at 80°C and the 180 degree peel adhesion force of the adhesive tape to an SUS plate is 15 N / 25 mm or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive tape. [Background technology]

[0002] Adhesive tapes are used for the assembly of portable electronic devices such as mobile phones and personal digital assistants (PDAs) (for example, Patent Documents 1 and 2). Adhesive tapes are also used for bonding optical members (for example, Patent Document 3). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2009-242541 A [Patent Document 2] JP 2009-258274 A [Patent Document 3] JP 2012-214544 A Summary of the Invention [Problem to be solved by the invention]

[0004] Global warming caused by greenhouse gases is an environmental issue that must be considered on a global scale. Recently, the idea of ​​carbon neutrality, which means that the total of greenhouse gas emissions minus the amount absorbed and removed is zero, is becoming more widespread around the world. In the field of electronic devices, which uses adhesive tape as a component, the movement to create environmentally friendly products is accelerating. The adhesive used to form the adhesive layer of the adhesive tape usually contains a solvent, and therefore, in the manufacturing process of the adhesive tape, CO2 is emitted from the solvent. Although the CO2 emitted in the manufacturing process can be reduced by reducing the amount of solvent contained in the adhesive, there is a problem that the viscosity of the adhesive increases and the processability decreases when the amount of solvent is simply reduced. In order to reduce the amount of solvent, that is, to prevent the viscosity from increasing even when the solid content ratio of the adhesive is increased, it is necessary to reduce the molecular weight of the components such as (meth)acrylic copolymers contained in the adhesive. On the other hand, the functions required for the adhesive layer include retention performance consisting of bulk cohesive strength and heat resistance, and adhesion consisting of interface wettability and bulk fluidity, and the components such as (meth)acrylic copolymers used in conventional adhesives had to have a molecular weight of about 500,000 or more to satisfy these performances.

[0005] An object of the present invention is to provide a pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer that is excellent in holding performance and adhesiveness while using a (meth)acrylic copolymer having a low molecular weight. [Means for solving the problem]

[0006] Disclosure 1 is an adhesive tape having an adhesive layer, the adhesive layer containing a crosslinked product of an adhesive comprising a (meth)acrylic copolymer, a crosslinking agent and a tackifier resin, wherein the (meth)acrylic copolymer obtained by alkaline decomposition of crosslinking points of the crosslinked product has a weight average molecular weight of 80,000 or more and less than 500,000 in a molecular weight range of 5,000 or more when GPC measurement is performed with RI detection using a differential refractometer, the weight average molecular weight of the (meth)acrylic copolymer is 80,000 or more and less than 500,000 in a molecular weight range of 5,000 or more, the adhesive tape is adhered to a SUS plate and in a retention test in which a load of 1 kg is applied in the shear direction at 80°C for 24 hours, the adhesive tape does not fall, and the 180° peel adhesion strength of the adhesive tape against the SUS plate is 15 N / 25 mm or more. Disclosure 2 is a pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer, the pressure-sensitive adhesive layer containing a crosslinked product of a pressure-sensitive adhesive comprising a (meth)acrylic copolymer, a crosslinking agent, and a tackifier resin, the (meth)acrylic copolymer obtained by alkaline decomposition of crosslinking points of the crosslinked product has a weight average molecular weight of 80,000 or more and less than 500,000 in a molecular weight range of 5,000 or more when GPC measurement is performed with RI detection using a differential refractometer, and the pressure-sensitive adhesive tape satisfies the following first configuration, the following second configuration, or the following third configuration: First configuration: the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the pressure-sensitive adhesive layer has a gel fraction of 5% by mass or more. Second configuration: the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent per 100 parts by mass of the (meth)acrylic copolymer, the gel fraction of the pressure-sensitive adhesive layer is less than 5% by mass, and the value obtained by subtracting the weight average molecular weight of the (meth)acrylic copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product in a molecular weight range of 5000 or more in a GPC measurement by RI detection with a differential refractometer from the weight average molecular weight of the sol component in a molecular weight range of 5000 or more in a GPC measurement by RI detection with a differential refractometer is 80,000 or more. Third configuration: the pressure-sensitive adhesive contains 0.1 parts by mass or more and less than 6 parts by mass of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the pressure-sensitive adhesive layer exceeds 30% by mass. Disclosure 3 is the pressure-sensitive adhesive tape of Disclosure 2, which satisfies the first configuration described above. Disclosure 4 is the pressure-sensitive adhesive tape of Disclosure 2, which satisfies the second configuration described above. Disclosure 5 is the pressure-sensitive adhesive tape of Disclosure 2, which satisfies the above-mentioned third configuration. The present disclosure 6 is the pressure-sensitive adhesive tape according to the present disclosure 1, wherein the pressure-sensitive adhesive layer satisfies the following first configuration, the following second configuration, or the following third configuration. First configuration: the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the pressure-sensitive adhesive layer has a gel fraction of 5% by mass or more. Second configuration: the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent per 100 parts by mass of the (meth)acrylic copolymer, the gel fraction of the pressure-sensitive adhesive layer is less than 5% by mass, and the value obtained by subtracting the weight average molecular weight of the (meth)acrylic copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product in a molecular weight range of 5000 or more in a GPC measurement by RI detection with a differential refractometer from the weight average molecular weight of the sol component in a molecular weight range of 5000 or more in a GPC measurement by RI detection with a differential refractometer is 80,000 or more. Third configuration: the pressure-sensitive adhesive contains 0.1 parts by mass or more and less than 6 parts by mass of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the pressure-sensitive adhesive layer exceeds 30% by mass. Disclosure 7 is a pressure-sensitive adhesive tape according to Disclosure 2 or 6, wherein the pressure-sensitive adhesive layer has a first configuration in which the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent per 100 parts by mass of the (meth)acrylic copolymer and the gel fraction of the pressure-sensitive adhesive layer is 5% by mass or more and less than 30% by mass, or a third configuration in which the pressure-sensitive adhesive contains 1.5 parts by mass or more and less than 6 parts by mass of the crosslinking agent per 100 parts by mass of the (meth)acrylic copolymer and the gel fraction of the pressure-sensitive adhesive layer exceeds 30% by mass. The present disclosure 8 is the pressure-sensitive adhesive tape of the present disclosure 7, wherein the pressure-sensitive adhesive layer has, as the first configuration, a configuration in which the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent per 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the pressure-sensitive adhesive layer is 5% by mass or more and less than 30% by mass. Present Disclosure 9 is the pressure-sensitive adhesive tape of Present Disclosure 7, wherein the pressure-sensitive adhesive layer has, as the third configuration, a configuration in which the pressure-sensitive adhesive contains 1.5 parts by mass or more and less than 6 parts by mass of the crosslinking agent per 100 parts by mass of the (meth)acrylic copolymer, and the pressure-sensitive adhesive layer has a gel fraction of more than 30% by mass. The present disclosure 10 is a pressure-sensitive adhesive tape according to the present disclosure 1, 2, 3, 4, 5, 6, 7, 8 or 9, in which, when the sol component of the pressure-sensitive adhesive layer is subjected to GPC measurement using RI detection with a differential refractometer, the weight average molecular weight of the sol component in the molecular weight range of 5,000 or more is 50,000 or more and 500,000 or less. The present disclosure 11 is a pressure-sensitive adhesive tape according to the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10, wherein, when a (meth)acrylic copolymer obtained by alkaline decomposition of the crosslinking points of the above-mentioned crosslinked product is subjected to GPC measurement with RI detection using a differential refractometer, the (meth)acrylic copolymer has a peak top molecular weight of 70,000 or more and 300,000 or less in a molecular weight region of 5,000 or more. The present disclosure 12 is an adhesive tape according to the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or 11, wherein the adhesive contains 0.03 mass% or more of a compound having a hydroxyl group in the solid content and 2 mass% or more of a compound having a carboxy group in the solid content. The present disclosure 13 is the pressure-sensitive adhesive tape of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12, wherein the (meth)acrylic copolymer has 50 mass % or more of structural units derived from a monomer having an alkyl group having 6 or more carbon atoms. A fourteenth aspect of the present disclosure is the pressure-sensitive adhesive tape of any one of the first, second, third, fourth, fifth, sixth, seventh, eighth, nineth, tenth, eleventh, twelveth, and thirteenth aspects of the present disclosure, wherein the pressure-sensitive adhesive layer has a glass transition temperature of -10°C or higher and 30°C or lower. The present disclosure 15 relates to a pressure-sensitive adhesive layer having a storage modulus G'(80°C) of 1.0 x 10 4 The pressure-sensitive adhesive tape of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, or 14, wherein the compressive strength is 100 Pa or more. A sixteenth aspect of the present disclosure is the pressure-sensitive adhesive tape of any one of the first, second, third, fourth, fifth, sixth, seventh, eighth, nineth, tenth, eleventh, twelveth, thirteenth, fourteenth, or fifteenth aspects of the present disclosure, wherein the pressure-sensitive adhesive layer has a thickness of 10 μm or more and 100 μm or less. The present disclosure 17 is the pressure-sensitive adhesive tape of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or 16, wherein the pressure-sensitive adhesive tape has a substrate, the substrate being a polyester resin film or a polypropylene resin film, and the substrate having a thickness of 5 μm or more and 200 μm or less. Disclosure 18 is the pressure-sensitive adhesive tape of Disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, or 17, wherein the pressure-sensitive adhesive tape has a substrate and has the pressure-sensitive adhesive layers on both sides of the substrate. The present invention will be described in detail below. The adhesive tape of Disclosure 1 is also referred to as the "adhesive tape of Invention 1," and the adhesive tape of Disclosure 2 is also referred to as the "adhesive tape of Invention 2." Furthermore, matters common to the adhesive tape of Invention 1 and the adhesive tape of Invention 2 are not particularly specified, or are described as the "adhesive tape of the present invention."

[0007] The inventors have discovered that even when an adhesive containing a (meth)acrylic copolymer having a specific low molecular weight is used to form an adhesive layer, by making the adhesive layer have a specific structure, it is possible to obtain an adhesive tape having an adhesive layer with excellent retention performance and adhesiveness, and have thus completed the present invention.

[0008] The pressure-sensitive adhesive tape of the present invention is a pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer contains a crosslinked product of a pressure-sensitive adhesive that includes a (meth)acrylic copolymer, a crosslinking agent, and a tackifier resin. In this specification, "(meth)acrylic" means acrylic or methacrylic.

[0009] In the pressure-sensitive adhesive layer of the present invention, the weight average molecular weight of the (meth)acrylic copolymer obtained by alkaline decomposition of the crosslinking points of the crosslinked product is 80,000 or more and less than 500,000 when GPC measurement is performed with RI detection using a differential refractometer. The weight average molecular weight of the (meth)acrylic copolymer in the molecular weight range of 5,000 or more (hereinafter, also simply referred to as "weight average molecular weight of the (meth)acrylic copolymer obtained by alkaline decomposition") is 80,000 or more and less than 500,000. When the weight-average molecular weight of the (meth)acrylic copolymer obtained by the alkaline decomposition is 80,000 or more, the bulk cohesive force in the obtained adhesive layer is large, and the adhesive layer has excellent heat resistance. When the weight-average molecular weight of the (meth)acrylic copolymer obtained by the alkaline decomposition is less than 500,000, the viscosity of the adhesive used to form the adhesive layer can be reduced, the processability can be improved, and the amount of solvent that is the source of CO2 emitted in the manufacturing process can be reduced. The preferred lower limit of the weight-average molecular weight of the (meth)acrylic copolymer obtained by the alkaline decomposition is 100,000, more preferably 150,000, and the preferred upper limit is 490,000, more preferably 450,000, and even more preferably 400,000. In this specification, the "(meth)acrylic copolymer obtained by alkali decomposition" may be the (meth)acrylic copolymer contained in the pressure-sensitive adhesive, or may be another compound. Examples of other compounds include (meth)acrylic copolymers in which a part of the structure of the (meth)acrylic copolymer contained in the pressure-sensitive adhesive is modified and / or deleted. The crosslinking points of the crosslinked product are decomposed with an alkali by the following method. That is, 300 mg of the above pressure-sensitive adhesive layer, 6 mL of ethanol, and 7 mL of 60% KOH aqueous solution are placed in a pressure vessel and subjected to pressure hydrolysis in an oven at 160° C. for 60 hours to alkali-decompose the crosslinking points of the crosslinked product and obtain a (meth)acrylic copolymer. When the (meth)acrylic copolymer obtained by alkali decomposition of the crosslinking points of the above crosslinked product is subjected to GPC measurement by RI detection using a differential refractometer, for example, the following method can be adopted. That is, the (meth)acrylic copolymer obtained by alkaline decomposition of the crosslinking points of the crosslinked product is analyzed by gel permeation chromatography (GPC) (manufactured by Waters, "2690 Separations Model") to measure the molecular weight distribution in terms of polystyrene. The GPC can be performed under the following conditions. Eluent: tetrahydrofuran (THF) Flow rate: 0.4mL / min Detector: RI differential refractometer Column: LF-804 (Shoko) Column temperature (measurement temperature): 40℃ Injection volume: 20μL

[0010] In the pressure-sensitive adhesive layer of the present invention, the peak top molecular weight of the (meth)acrylic copolymer obtained by alkaline decomposition of the crosslinking points of the crosslinked product in a molecular weight range of 5,000 or more when GPC measurement is performed with RI detection using a differential refractometer (hereinafter, also simply referred to as "peak top molecular weight of the (meth)acrylic copolymer obtained by alkaline decomposition") is preferably 70,000 in lower limit and 300,000 in upper limit. When the peak top molecular weight of the (meth)acrylic copolymer obtained by the alkaline decomposition is 70,000 or more, the bulk cohesive force in the obtained adhesive layer becomes larger, and the adhesive layer becomes more excellent in heat resistance. When the peak top molecular weight of the (meth)acrylic copolymer obtained by the alkaline decomposition is 300,000 or less, the viscosity of the adhesive used to form the adhesive layer can be lowered, the processability can be improved, and the amount of solvent that is the source of CO2 emitted in the manufacturing process can be reduced. The peak top molecular weight of the (meth)acrylic copolymer obtained by the alkaline decomposition is more preferably 80,000 in lower limit, more preferably 100,000 in lower limit, more preferably 250,000 in upper limit, and even more preferably 230,000 in upper limit. In this specification, the "peak top molecular weight" means the molecular weight at the highest peak in the molecular weight distribution curve. Even if the molecular weight distribution curve has a shoulder or two or more peaks, the peak top molecular weight means the molecular weight at the highest peak in the molecular weight distribution curve.

[0011] In the pressure-sensitive adhesive layer of the present invention, from the viewpoint of adjusting the molecular weight distribution, the polydispersity of the (meth)acrylic copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product in a molecular weight region of 5,000 or more when the (meth)acrylic copolymer is subjected to GPC measurement with RI detection using a differential refractometer (hereinafter also simply referred to as "polydispersity of the (meth)acrylic copolymer obtained by alkali decomposition") is preferably 15,000 in lower limit, and preferably 100,000 in upper limit, more preferably 60,000 in upper limit. The polydispersity refers to the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn).

[0012] In the pressure-sensitive adhesive tape of the present invention, the weight-average molecular weight of the sol component in the pressure-sensitive adhesive layer in the region of molecular weight 5000 or more when the sol component is subjected to GPC measurement by RI detection with a differential refractometer (hereinafter, also simply referred to as "weight-average molecular weight of the sol component") is preferably 50,000 at the lower limit and 500,000 at the upper limit. When the weight-average molecular weight of the sol component is 50,000 or more, the bulk cohesive force in the obtained pressure-sensitive adhesive layer becomes larger, and the pressure-sensitive adhesive layer becomes more excellent in heat resistance and high-temperature repulsion resistance. When the weight-average molecular weight of the sol component is 500,000 or less, the viscosity of the pressure-sensitive adhesive used to form the pressure-sensitive adhesive layer can be lowered, the processability can be further improved, and the amount of the solvent that is the source of CO2 emitted in the manufacturing process can be further reduced. The weight-average molecular weight of the sol component is more preferably 70,000 at the lower limit, more preferably 100,000 at the lower limit, more preferably 400,000 at the upper limit, and even more preferably 300,000 at the upper limit. Here, the "sol component" refers to a component remaining after removing the "gel component" from the pressure-sensitive adhesive layer. The "gel component" is a low-fluidity component remaining on the mesh in the gel fraction measurement process, in which the (meth)acrylic copolymer, the tackifier resin described below, and the like form a crosslinked structure via a crosslinking agent described below, and the "sol component" is a high-fluidity component remaining after removing the gel component in the process. The sol component of the pressure-sensitive adhesive layer can be obtained, for example, by immersing the pressure-sensitive adhesive layer in tetrahydrofuran (THF) at 23° C. for 24 hours, filtering the insoluble matter through a 200-mesh wire screen, and removing the gel component. When the sol component of the pressure-sensitive adhesive layer is subjected to GPC measurement by RI detection using a differential refractometer, for example, the following method can be adopted. That is, the sol component of the pressure-sensitive adhesive layer is analyzed by gel permeation chromatography (GPC) (manufactured by Waters, "2690 Separations Model") to measure the molecular weight distribution in terms of polystyrene. The GPC can be performed under the following conditions. Eluent: tetrahydrofuran (THF) Flow rate: 0.4mL / min Detector: RI differential refractometer Column: LF-804 (Shoko) Column temperature (measurement temperature): 40℃ Injection volume: 20μL

[0013] In the pressure-sensitive adhesive tape of the present invention, the pressure-sensitive adhesive layer has a peak top molecular weight of the sol component in a molecular weight range of 5000 or more (hereinafter, simply referred to as "peak top molecular weight of the sol component") of 30,000 or less, and a preferred upper limit of 300,000 or less, when the sol component of the pressure-sensitive adhesive layer is subjected to GPC measurement by RI detection using a differential refractometer. When the peak top molecular weight of the sol component is 30,000 or more, the bulk cohesive force of the obtained pressure-sensitive adhesive layer becomes larger, and the pressure-sensitive adhesive layer has better heat resistance. When the peak top molecular weight of the sol component is 300,000 or less, the viscosity of the pressure-sensitive adhesive used to form the pressure-sensitive adhesive layer can be lowered, the processability can be improved, and the amount of the solvent that is the source of CO2 emitted in the manufacturing process can be reduced. A more preferred lower limit of the peak top molecular weight of the sol component is 70,000, a more preferred lower limit is 80,000, a more preferred upper limit is 250,000, and a more preferred upper limit is 230,000.

[0014] The adhesive tape of the present invention 1 does not fall when a retention test is performed in which a load of 1 kg is applied in the shear direction at 80° C. for 24 hours after bonding to a SUS plate. The adhesive tape that shows the results of the retention test as described above has excellent heat resistance and, for example, is well fixed to members used in electronic devices. As a result of the retention test, it is preferable that there is no deviation of 1 mm or more, and more preferably no deviation of 0.5 mm or more. In addition, the adhesive tape of the present invention 2 preferably does not fall when a retention test is performed in which a load of 1 kg is applied in the shear direction at 80° C. for 24 hours after bonding with a SUS plate. The adhesive tape showing the results of the retention test as described above has better heat resistance, and for example, is better fixed to members used in electronic devices. As a result of the retention test, it is more preferable that there is no deviation of 1 mm or more, and even more preferable that there is no deviation of 0.5 mm or more. The retention test can be carried out by the following method: A schematic diagram showing the retention test method is shown in FIG. That is, first, the adhesive tape 1 is cut into strips of 25 mm width, and then bonded to the SUS plate 2 by moving a 2 kg rubber roller back and forth at a speed of 300 mm / min. Next, a cut is made in the adhesive tape 1 so that the adhesive area is 25 mm x 25 mm. After that, it is left to stand at 23°C for 20 minutes, placed in an oven at 80°C, heated for another 15 minutes, and then, while maintaining the temperature at 80°C, a load of 1 kg is applied in the shear direction using a 1 kg weight 3 as shown in Figure 1. It is checked whether the adhesive tape has fallen off, and if it has not fallen off after 24 hours, the amount of movement (displacement) from the cut position is measured with a scale magnifying glass.

[0015] The adhesive tape of the present invention 1 has a 180° peel adhesion of the adhesive tape to a SUS plate of 15 N / 25 mm or more. Specifically, after being laminated to a SUS plate, the 180° peel adhesion is 15 N / 25 mm or more when a tensile test in the 180° direction is performed at 23° C. and a peel speed of 300 mm / min according to JIS Z0237. By having the 180° peel adhesion of 15 N / 25 mm or more, the adhesive tape can have sufficient adhesiveness, and for example, can be well fixed to a member used in an electronic device. The 180° peel adhesion is preferably 18 N / 25 mm or more, more preferably 20 N / 25 mm or more. In addition, the adhesive tape of the present invention 2 preferably has a 180° peel adhesion of the adhesive tape to a SUS plate of 15 N / 25 mm or more. Specifically, after being laminated to a SUS plate, the 180° peel adhesion is preferably 15 N / 25 mm or more when a tensile test in the 180° direction is performed under conditions of 23° C. and a peel speed of 300 mm / min according to JIS Z0237. By having the 180° peel adhesion of 15 N / 25 mm or more, the adhesive tape can have more sufficient adhesiveness, and for example, the adhesive tape can be better fixed to a member used in an electronic device. The 180° peel adhesion is more preferably 18 N / 25 mm or more, and even more preferably 20 N / 25 mm or more. The 180° peel adhesion can be measured by the following method. That is, first, the adhesive tape is cut into strips of 25 mm width, and then laminated to a SUS plate by moving a 2 kg rubber roller back and forth at a speed of 300 mm / min. Then, the tape is left to stand for 20 minutes at a temperature of 23°C and a relative humidity of 50% to obtain a test piece. The obtained test piece is subjected to a tensile test using a tensile tester in accordance with JIS Z0237 under the conditions of 23°C, a peel speed of 300 mm / min, and a peel angle of 180°, so that the above-mentioned 180° peel adhesive strength can be measured.

[0016] In the pressure-sensitive adhesive tape of invention 2, the pressure-sensitive adhesive layer satisfies the following first configuration, the following second configuration, or the following third configuration. In addition, in the pressure-sensitive adhesive tape of invention 1, it is preferable that the pressure-sensitive adhesive layer satisfies the following first configuration, the following second configuration, or the following third configuration. First configuration: the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the pressure-sensitive adhesive layer has a gel fraction of 5% by mass or more. Second configuration: the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent per 100 parts by mass of the (meth)acrylic copolymer, the gel fraction of the pressure-sensitive adhesive layer is less than 5% by mass, and the value obtained by subtracting the weight average molecular weight of the (meth)acrylic copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product in a molecular weight range of 5000 or more in a GPC measurement by RI detection with a differential refractometer from the weight average molecular weight of the sol component in a molecular weight range of 5000 or more in a GPC measurement by RI detection with a differential refractometer is 80,000 or more. Third configuration: the pressure-sensitive adhesive contains 0.1 parts by mass or more and less than 6 parts by mass of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the pressure-sensitive adhesive layer exceeds 30% by mass. In the pressure-sensitive adhesive tape of invention 2, when the pressure-sensitive adhesive layer satisfies the first, second, or third configuration, the resulting pressure-sensitive adhesive layer has excellent retention performance and adhesiveness. Also, in the pressure-sensitive adhesive tape of invention 1, when the pressure-sensitive adhesive layer satisfies the first, second, or third configuration, the resulting pressure-sensitive adhesive layer has even more excellent retention performance and adhesiveness.

[0017] In the first configuration, if the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent per 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the pressure-sensitive adhesive layer is 5% by mass or more, the bulk cohesive force of the resulting pressure-sensitive adhesive layer is large, and the pressure-sensitive adhesive layer has excellent heat resistance. This is because, even if the molecular weight of the (meth)acrylic copolymer is small and the gel fraction is low, if the number of crosslinking agents is large, crosslinking and high molecular weight in the sol component can be considered to have progressed. In the first configuration, the gel fraction of the pressure-sensitive adhesive layer is preferably 10% by mass or more, more preferably 15% by mass or more. The gel fraction of the pressure-sensitive adhesive layer in the first, second and third configurations can be measured by, for example, the following method. That is, first, W1 (g) of the pressure-sensitive adhesive layer is collected, the collected pressure-sensitive adhesive layer is immersed in ethyl acetate at 23°C for 24 hours, and the insoluble matter is filtered through a 200-mesh wire net. The residue on the wire net is dried by heating at 110°C, and the mass W2 (g) of the resulting dried residue is measured. The gel fraction (degree of crosslinking) is calculated from the obtained W1 and W2 using the following formula (I). Gel fraction (mass%) = 100 × W2 / W1(I)

[0018] In the first configuration, the gel fraction of the pressure-sensitive adhesive layer is preferably less than 30% by mass. In the first configuration, the gel fraction of the pressure-sensitive adhesive layer is less than 30% by mass, which suppresses a decrease in bulk fluidity due to an increase in the elastic modulus of the pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer has excellent adhesiveness without significantly decreasing the wettability of the interface. In the first configuration, the gel fraction of the pressure-sensitive adhesive layer is more preferably 28% by mass or less.

[0019] In the first configuration, the content of the crosslinking agent in the pressure-sensitive adhesive is preferably 12 parts by mass or less per 100 parts by mass of the (meth)acrylic copolymer. In the first configuration, the content of the crosslinking agent in the pressure-sensitive adhesive is 12 parts by mass or less, which suppresses a decrease in bulk fluidity due to an increase in the elastic modulus of the pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer has excellent adhesion without significantly decreasing the wettability of the interface. In the first configuration, the content of the crosslinking agent in the pressure-sensitive adhesive is more preferably 10 parts by mass or less.

[0020] In the second configuration, when the sol component of the pressure-sensitive adhesive layer is subjected to GPC measurement by RI detection using a differential refractometer, the weight average molecular weight of the sol component in the molecular weight range of 5000 or more minus the weight average molecular weight of the (meth)acrylic copolymer obtained by the alkali decomposition is 80,000 or more. As a result, even if the gel fraction of the pressure-sensitive adhesive layer is small, crosslinking of the polymer in the sol component progresses to increase the molecular weight, and the pressure-sensitive adhesive layer has a high bulk cohesive force. In the second configuration, the preferred lower limit of the gel fraction of the pressure-sensitive adhesive layer is 0.1% by mass, and the more preferred lower limit is 1% by mass. In addition, in the second configuration, the preferred lower limit of the value obtained by subtracting the weight average molecular weight of the (meth)acrylic copolymer obtained by the alkali decomposition from the weight average molecular weight of the sol component is 100,000, and the more preferred lower limit is 120,000.

[0021] In the third configuration, when the gel fraction of the pressure-sensitive adhesive layer exceeds 30% by mass, the pressure-sensitive adhesive layer has a large bulk cohesive force and has excellent heat resistance. In the third configuration, the gel fraction of the pressure-sensitive adhesive layer is preferably 31% by mass or more, more preferably 35% by mass or more, even more preferably 40% by mass or more, and even more preferably 45% by mass or more. In the third configuration, the pressure-sensitive adhesive layer preferably has a gel fraction of 70% by mass or less. In the third configuration, the pressure-sensitive adhesive layer has a gel fraction of 70% by mass or less, which suppresses a decrease in bulk fluidity in the pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer has excellent adhesiveness without significantly decreasing wettability at the interface. In the third configuration, the pressure-sensitive adhesive layer more preferably has a gel fraction of 65% by mass or less, and even more preferably has a gel fraction of 60% by mass or less. In the third configuration, the content of the crosslinking agent in the pressure-sensitive adhesive is preferably 0.1 parts by mass or more relative to 100 parts by mass of the (meth)acrylic copolymer. In the third configuration, the content of the crosslinking agent in the pressure-sensitive adhesive is 0.1 parts by mass or more, so that the gel fraction of the resulting pressure-sensitive adhesive layer is likely to increase, and the bulk cohesive force is greater. In the third configuration, the content of the crosslinking agent in the pressure-sensitive adhesive is more preferably 1.5 parts by mass or more, and even more preferably 2 parts by mass or more.

[0022] The pressure-sensitive adhesive layer preferably has a first configuration in which the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent per 100 parts by mass of the (meth)acrylic copolymer and the pressure-sensitive adhesive layer has a gel fraction of 5% by mass or more and less than 30% by mass, or a third configuration in which the pressure-sensitive adhesive contains 1.5 parts by mass or more and less than 6 parts by mass of the crosslinking agent per 100 parts by mass of the (meth)acrylic copolymer and the pressure-sensitive adhesive layer has a gel fraction of more than 30% by mass.

[0023] Regarding the pressure-sensitive adhesive layer, the method of adjusting the weight average molecular weight, peak top molecular weight, and polydispersity of the (meth)acrylic copolymer obtained by the alkali decomposition, the weight average molecular weight and peak top molecular weight of the sol component, and the value obtained by subtracting the weight average molecular weight of the (meth)acrylic copolymer obtained by the alkali decomposition from the weight average molecular weight of the sol component to the above-mentioned range is not particularly limited. Specifically, for example, a method of using a (meth)acrylic copolymer obtained by a polymerization method such as living radical polymerization or free radical polymerization as the (meth)acrylic copolymer contained in the pressure-sensitive adhesive can be mentioned. Among them, from the viewpoint of shortening the reaction time and suppressing costs, a method of using a (meth)acrylic copolymer obtained by free radical polymerization is preferable. In addition, from the viewpoint of uniformly introducing crosslinking points, living radical polymerization is preferable. When the crosslinking points are uniformly introduced, the pressure-sensitive adhesive layer obtained has a uniform crosslinking structure, the cohesive force of the bulk increases, and the creep resistance is improved. On the other hand, if the cohesive force of the bulk becomes too large, the flexibility of the pressure-sensitive adhesive layer is impaired and the adhesive force to the interface decreases. Furthermore, by controlling the weight average molecular weight of the (meth)acrylic copolymer obtained by the above polymerization method, it is possible to adjust the weight average molecular weight and peak top molecular weight of the (meth)acrylic copolymer obtained by the above alkaline decomposition.

[0024] Among the (meth)acrylic copolymers obtained by the above polymerization methods, it is preferable to use a (meth)acrylic copolymer obtained under relatively mild polymerization conditions such as keeping the polymerization temperature and the concentration of the monomer mixture constant. This makes it possible to make the composition of the (meth)acrylic copolymer more uniform, or to reduce the polydispersity of the (meth)acrylic copolymer obtained by the above alkali decomposition, and makes it easier to adjust the molecular weight distribution of the sol component of the pressure-sensitive adhesive layer. Examples of polymerization methods that provide such relatively mild polymerization conditions include a method of performing free radical constant temperature polymerization, and a method of free radical boiling point polymerization in which half of the monomer mixture and a polymerization initiator are added into a reactor to start polymerization, and then the remaining half of the monomer mixture is added dropwise or all at once.

[0025] In the above polymerization method, the reaction is preferably carried out for 2 to 10 hours. If the polymerization time is not properly adjusted, the crosslinking points of the polymer chain may be introduced non-uniformly due to the high reaction rate of the crosslinkable functional group-containing monomer in the free radical polymerization, or a large amount of residual monomer may remain, resulting in a decrease in creep resistance. The polymerization reaction time in the polymerization method is preferably 2 hours at the lower limit and 10 hours at the upper limit. By setting the polymerization reaction time in this range, it becomes easier to adjust the weight average molecular weight of the (meth)acrylic copolymer obtained by the alkaline decomposition to the above-mentioned range. The polymerization reaction time is more preferably 3 hours at the lower limit and 8 hours at the upper limit.

[0026] Examples of the polymerization initiator used in the above polymerization method include azo compounds and organic peroxides. Examples of the azo compound include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1-azobis(cyclohexane-1-carbonitrile), 1-((1-cyano-1-methylethyl)azo)formamide, 4,4' -Azobis(4-cyanovaleric acid), dimethyl-2,2'-azobis(2-methylpropionate), dimethyl-1,1'-azobis(1-cyclohexanecarboxylate), 2,2'-azobis(2-methyl-N-(1,1'-bis(hydroxymethyl)-2-hydroxyethyl)propionamide), 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide), 2,2 '-Azobis(N-(2-propenyl)-2-methylpropionamide), 2,2'-Azobis(N-butyl-2-methylpropionamide), 2,2'-Azobis(N-cyclohexyl-2-methylpropionamide), 2,2'-Azobis(2-(2-imidazolin-2-yl)propane) dihydrochloride, 2,2'-Azobis(2-(1-(2-hydroxyethyl)-2-imidazolin-2-yl)propane) ) dihydrochloride, 2,2'-azobis(2-(2-imidazolin-2-yl)propane), 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(N-(2-carboxyethyl)-2-methylpropionamidine) tetrahydrate, 2,2'-azobis(1-imino-1-pyrrolidino-2-methylpropane) dihydrochloride, 2,2'-azobis(2,4,4-trimethylpentane), etc. These azo compounds may be used alone or in combination of two or more. Examples of the organic peroxides include 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane, t-hexylperoxypivalate, t-butylperoxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyisobutyrate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, etc. These organic peroxides may be used alone or in combination of two or more.

[0027] Among the above polymerization initiators, polymerization initiators having a functional group are preferred. By using the polymerization initiator having the functional group, a functional group can be introduced to the end of the (meth)acrylic copolymer, and in particular, a functional group can be introduced to the end of a molecular chain having a relatively small molecular weight and a small number of structural units derived from a crosslinkable functional group-containing monomer in the (meth)acrylic copolymer. Since such low molecular chains have a functional group at the end and are incorporated into a crosslinked structure via a crosslinking agent described later, the bulk cohesive force in the obtained adhesive layer becomes larger, and the adhesive layer has better heat resistance. Even if the low molecular chains are not involved in the crosslinked structure, the low molecular chains can form a bond (e.g., a dimer) between themselves via a crosslinking agent described later or a bond between a crosslinking agent described later and a tackifier resin described later by having a functional group at the end. In such a case, it can be said that the (meth)acrylic copolymer contained in the sol component of the adhesive layer has a high molecular weight as a whole. Therefore, it becomes easier to adjust the weight average molecular weight, etc. of the sol component to the above-mentioned range, and the bulk cohesive force in the obtained adhesive layer becomes larger, and the adhesive layer has better heat resistance. Examples of the functional group include a hydroxyl group, a carboxyl group, a silyl group, a glycidyl group, an amino group, an amide group, a nitrile group, an alkoxy group, and an acetoacetyl group. Among these, a hydroxyl group and a carboxyl group are preferable. Examples of the polymerization initiator having the functional group include 2,2'-azobis(2-methyl-N-(1,1'-bis(hydroxymethyl)-2-hydroxyethyl)propionamide) and 4,4'-azobis(4-cyanovaleric acid (valeric acid)). These polymerization initiators having functional groups may be used alone or in combination of two or more.

[0028] The amount of the polymerization initiator added is preferably 0.01 parts by mass at the lower limit and 0.5 parts by mass at the upper limit with respect to 100 parts by mass of the monomer mixture. By setting the amount of the polymerization initiator within this range, it becomes easier to adjust the weight average molecular weight of the sol component within the above-mentioned range. The more preferred lower limit of the amount of the polymerization initiator added is 0.02 parts by mass, and the more preferred upper limit is 0.3 parts by mass.

[0029] In the above free radical polymerization, a chain transfer agent may be used. Examples of the chain transfer agent include thiol compounds such as lauryl mercaptan, mercaptopropionic acid, mercaptosuccinic acid, 3-mercapto-1,2-propanediol, 1-butanethiol, cyclohexyl 3-mercaptopropionate, 2-ethylhexyl mercaptoacetate, 1-hexadecanethiol, 2-mercaptoethanol, mercaptoacetic acid, ethyl mercaptoacetate, 1-octanethiol, tridecyl 3-mercaptopropionate, and thiophenol. In addition, 2,4-diphenyl-4-methyl-1-pentene and the like can be used. These chain transfer agents may be used alone or in combination of two or more.

[0030] Of the above chain transfer agents, it is preferable to use a chain transfer agent having a functional group. By using the chain transfer agent having the functional group, it becomes easier to adjust the weight average molecular weight and the like of the sol component to fall within the above-mentioned range. In other words, by using a chain transfer agent having the above-mentioned functional group, a functional group can be introduced to the end of the low molecular chain, just as in the case of using a polymerization initiator having the above-mentioned functional group, and as a result, the bulk cohesive force of the obtained pressure-sensitive adhesive layer becomes greater, and the pressure-sensitive adhesive layer becomes more excellent in creep resistance. Examples of the functional group include hydroxyl group, carboxyl group, silyl group, glycidyl group, amino group, amide group, nitrile group, alkoxy group, acetoacetyl group, etc. Among them, hydroxyl group and carboxyl group are preferred, and hydroxyl group is more preferred. In particular, in a system in which carboxyl group is biased toward high molecular weight polymer chain, a chain transfer agent having hydroxyl group as a functional group is used to introduce hydroxyl group into the end of low molecular chain, so that the crosslinking reaction of low molecular chain can be promoted preferentially. The number of functional groups of the chain transfer agent having the functional group is preferably multivalent, since the crosslinked structure is easily made high-dimensional, the network is easily formed, and the bulk cohesion force in the pressure-sensitive adhesive layer is increased.As the chain transfer agent having the functional group, among the chain transfer agents described above, for example, mercaptopropionic acid, mercaptosuccinic acid, 3-mercapto-1,2-propanediol, etc. can be mentioned.These chain transfer agents having functional groups can be used alone or in combination of two or more.

[0031] The amount of the chain transfer agent added is preferably 0.01 parts by mass at the lower limit and 0.5 parts by mass at the upper limit with respect to 100 parts by mass of the monomer mixture. By setting the amount of the chain transfer agent in this range, it becomes easier to adjust the weight average molecular weight of the sol component to the above-mentioned range. The more preferred lower limit of the amount of the chain transfer agent added is 0.02 parts by mass, and the more preferred upper limit is 0.3 parts by mass.

[0032] In the above free radical polymerization, a dispersion stabilizer may be used. Examples of the dispersion stabilizer include polyvinylpyrrolidone, polyvinyl alcohol, methyl cellulose, ethyl cellulose, poly(meth)acrylic acid, poly(meth)acrylic acid ester, polyethylene glycol, etc. These dispersion stabilizers may be used alone or in combination of two or more kinds.

[0033] When a polymerization solvent is used in the above-mentioned free radical polymerization, the polymerization solvent may be, for example, a non-polar solvent such as hexane, cyclohexane, octane, toluene, xylene, etc., or a highly polar solvent such as water, methanol, ethanol, propanol, butanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, tetrahydrofuran, dioxane, N,N-dimethylformamide, etc. These polymerization solvents may be used alone or in combination of two or more kinds.

[0034] Moreover, the polymerization temperature in the above free radical polymerization is preferably 0° C. to 110° C. from the viewpoint of the polymerization rate.

[0035] The (meth)acrylic copolymer preferably has a structural unit derived from a monomer having an alkyl group with a carbon number of 6 or more. When the (meth)acrylic copolymer has a structural unit derived from a monomer having an alkyl group with a carbon number of 6 or more, the bulk of the pressure-sensitive adhesive layer becomes more flexible and the viscosity of the pressure-sensitive adhesive solution becomes lower, thereby further improving processability. The alkyl group having 6 or more carbon atoms in the monomer having an alkyl group having 6 or more carbon atoms preferably has a carbon number of 6 to 16. When the (meth)acrylic copolymer has a structural unit derived from a monomer having an alkyl group having 6 to 16 carbon atoms, the bulk fluidity of the obtained adhesive layer is increased, and the adhesive layer has better adhesion to a rough surface. The alkyl group having 6 or more carbon atoms in the monomer having an alkyl group having 6 or more carbon atoms more preferably has a carbon number of 6 to 12. In addition, the alkyl group having 6 or more carbon atoms in the monomer having an alkyl group having 6 or more carbon atoms may or may not have a branch, but it is preferable that the alkyl group has no branch. When the alkyl group of the monomer having an alkyl group having 6 or more carbon atoms has no branch, the adhesive layer has a low storage modulus at low to normal temperatures, but a high storage modulus at high temperatures, and therefore has better heat resistance and better adhesion to a rough surface.

[0036] Examples of the monomer having an alkyl group having 6 or more carbon atoms include alkyl (meth)acrylates having an alkyl group having 6 or more carbon atoms. Examples of the alkyl (meth)acrylate having an alkyl group having 6 or more carbon atoms include n-heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, myristyl (meth)acrylate, cetyl (meth)acrylate, isostearyl acrylate, and arachidyl (meth)acrylate. These alkyl (meth)acrylates having an alkyl group having 6 or more carbon atoms may be used alone or in combination of two or more. Among them, n-heptyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred. In this specification, the term "(meth)acrylate" means acrylate or methacrylate.

[0037] The preferred lower limit of the content of the structural unit derived from the monomer having an alkyl group with 6 or more carbon atoms in the (meth)acrylic copolymer is 50% by mass. When the content of the structural unit derived from the monomer having an alkyl group with 6 or more carbon atoms is 50% by mass or more, the glass transition temperature of the (meth)acrylic copolymer is lowered, the bulk fluidity of the obtained adhesive layer is increased, and the adhesive layer has better adhesion to rough surfaces. In addition, the bulk of the adhesive layer becomes softer, and the viscosity of the adhesive solution is further reduced, so that the processability is further improved. Furthermore, the compatibility with the tackifier resin described below is also improved. The more preferred lower limit of the content of the structural unit derived from the monomer having an alkyl group with 6 or more carbon atoms is 60% by mass, and the even more preferred lower limit is 70% by mass. In addition, the preferred upper limit of the content of the structural units derived from the monomer having an alkyl group with 6 or more carbon atoms in the (meth)acrylic copolymer is 98% by mass. By making the content of the structural units derived from the monomer having an alkyl group with 6 or more carbon atoms 98% by mass or less, the glass transition temperature of the (meth)acrylic copolymer is not too low, and the bulk cohesive force of the obtained pressure-sensitive adhesive layer is increased, resulting in a pressure-sensitive adhesive layer with superior heat resistance. The more preferred upper limit of the content of the structural units derived from the monomer having an alkyl group with 6 or more carbon atoms is 97% by mass, and even more preferred upper limit is 95% by mass.

[0038] The (meth)acrylic copolymer may have a structural unit derived from an alkyl (meth)acrylate having an alkyl group having 5 or less carbon atoms. Examples of the alkyl (meth)acrylate having an alkyl group having 5 or less carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, and butyl (meth)acrylate. These alkyl (meth)acrylates having an alkyl group having 5 or less carbon atoms may be used alone or in combination of two or more. Among them, butyl (meth)acrylate is preferred.

[0039] The content of the structural unit derived from the alkyl (meth)acrylate having an alkyl group with 5 or less carbon atoms is preferably 25% by mass or more and less than 50% by mass. When the content of the structural unit derived from the alkyl (meth)acrylate having an alkyl group with 5 or less carbon atoms is 25% by mass or more, the glass transition temperature of the (meth)acrylic copolymer is sufficiently high, so that the bulk cohesive force in the obtained adhesive layer is greater, and the adhesive layer has better heat resistance. When the content is less than 50% by mass, the glass transition temperature of the (meth)acrylic copolymer is not too high, so that the bulk fluidity in the obtained adhesive layer is increased, and the adhesive layer has better adhesion to rough surfaces. The more preferable lower limit of the content is 30% by mass, and the more preferable upper limit is 45% by mass.

[0040] The (meth)acrylic copolymer preferably has a structural unit derived from a crosslinkable functional group-containing monomer. The (meth)acrylic copolymer has a structural unit derived from the crosslinkable functional group-containing monomer, and the (meth)acrylic copolymer and the tackifier resin described below build a crosslinked structure via a crosslinking agent described below, so that the bulk cohesive force in the obtained adhesive layer becomes larger, and the adhesive layer has better heat resistance. Examples of the crosslinkable functional group include a hydroxyl group, a carboxyl group, a silyl group, a glycidyl group, an amino group, an amide group, a nitrile group, an alkoxy group, and an acetoacetyl group. Among them, a hydroxyl group and a carboxyl group are preferred because they are easy to adjust the bulk cohesive force in the adhesive layer.

[0041] Examples of the crosslinkable functional group-containing monomer having a hydroxyl group as the crosslinkable functional group include 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, and hydroxypropyl (meth)acrylate. Examples of the crosslinkable functional group-containing monomer having a carboxy group as the crosslinkable functional group include (meth)acrylic acid, itaconic acid, maleic anhydride, crotonic acid, maleic acid, fumaric acid, etc. Among these, acrylic acid is preferred. An example of the crosslinkable functional group-containing monomer having a glycidyl group as the crosslinkable functional group is glycidyl (meth)acrylate. Examples of the crosslinkable functional group-containing monomer having an amide group as the crosslinkable functional group include hydroxyethylacrylamide, isopropylacrylamide, and dimethylaminopropylacrylamide. Examples of the crosslinkable functional group-containing monomer having a nitrile group as the crosslinkable functional group include acrylonitrile.

[0042] The content ratio of the structural unit derived from the crosslinkable functional group-containing monomer in the (meth)acrylic copolymer is preferably 0.05% by mass at the lower limit, and 20% by mass at the upper limit. When the content ratio of the structural unit derived from the crosslinkable functional group-containing monomer is 0.05% by mass or more, the bulk cohesive force of the obtained pressure-sensitive adhesive layer becomes larger, and the pressure-sensitive adhesive layer has better heat resistance. When the content ratio of the structural unit derived from the crosslinkable functional group-containing monomer is 20% by mass or less, the bulk fluidity of the obtained pressure-sensitive adhesive layer increases, and the pressure-sensitive adhesive layer has better adhesion to rough surfaces. The more preferred lower limit of the content ratio of the structural unit derived from the crosslinkable functional group-containing monomer is 0.1% by mass, and the more preferred upper limit is 15% by mass.

[0043] When the (meth)acrylic copolymer has a structural unit derived from a crosslinkable functional group-containing monomer having a hydroxyl group as the crosslinkable functional group, the preferred lower limit of the content of the structural unit derived from the crosslinkable functional group-containing monomer is 0.03% by mass, and the preferred upper limit is 1% by mass. When the content of the structural unit derived from a crosslinkable functional group-containing monomer having a hydroxyl group as the crosslinkable functional group is 0.03% by mass or more, the bulk cohesive force in the obtained pressure-sensitive adhesive layer becomes larger, and the pressure-sensitive adhesive layer has better heat resistance. When the content of the structural unit derived from a crosslinkable functional group-containing monomer having a hydroxyl group as the crosslinkable functional group is 1% by mass or less, the gel fraction of the obtained pressure-sensitive adhesive layer does not become too high, and the pressure-sensitive adhesive layer has better adhesion to a rough surface. The content of the structural unit derived from a crosslinkable functional group-containing monomer having a hydroxyl group as the crosslinkable functional group is more preferably 0.05% by mass, even more preferably 0.06% by mass, and more preferably 0.5% by mass, even more preferably 0.3% by mass, and particularly preferably 0.1% by mass. In addition, when the (meth)acrylic copolymer has a constituent unit derived from a crosslinkable functional group-containing monomer having a carboxy group as the crosslinkable functional group, the preferred lower limit of the content of the constituent unit derived from the crosslinkable functional group-containing monomer is 2% by mass, and the preferred upper limit is 15% by mass. When the content of the constituent unit derived from the crosslinkable functional group-containing monomer having a carboxy group as the crosslinkable functional group is 2% by mass or more, the gel fraction of the obtained pressure-sensitive adhesive layer is likely to be high, and the glass transition temperature of the (meth)acrylic copolymer is sufficiently high, so that the bulk cohesive force in the obtained pressure-sensitive adhesive layer is larger. As a result, the pressure-sensitive adhesive layer has better heat resistance. When the content of the constituent unit derived from the crosslinkable functional group-containing monomer having a carboxy group as the crosslinkable functional group is 15% by mass or less, the glass transition temperature of the (meth)acrylic copolymer does not become too high, and the pressure-sensitive adhesive layer has better adhesion to a rough surface. The content of the structural unit derived from a crosslinkable functional group-containing monomer having a carboxy group as the crosslinkable functional group is more preferably 3% by mass, even more preferably 5% by mass, and more preferably 10% by mass, even more preferably 8% by mass.

[0044] The (meth)acrylic copolymer may, as necessary, have a constituent unit derived from the monomer having an alkyl group having 6 or more carbon atoms, a constituent unit derived from an alkyl (meth)acrylate having an alkyl group having 5 or less carbon atoms, and a constituent unit derived from another copolymerizable polymerizable monomer other than the constituent unit derived from the crosslinkable functional group-containing monomer.

[0045] The pressure-sensitive adhesive contains a crosslinking agent. As the crosslinking agent, for example, an isocyanate-based crosslinking agent, an aziridine-based crosslinking agent, an epoxy-based crosslinking agent, a metal chelate-type crosslinking agent, etc. are selected and used according to the type of crosslinkable functional group of the (meth)acrylic copolymer. Among them, an isocyanate-based crosslinking agent is preferred because it can selectively crosslink hydroxyl groups and carboxyl groups and is easy to control the crosslinked structure. In particular, it is preferred to include 80 parts by mass or more of an isocyanate-based crosslinking agent having two or more isocyanate groups in one molecule in 100 parts by mass of the crosslinking agent. Among the above-mentioned isocyanate-based crosslinking agents, examples of commercially available ones include Coronate HX, Coronate L (both manufactured by Tosoh Corporation), and Mytec NY260A (manufactured by Mitsubishi Chemical Corporation).

[0046] The number of functional groups of the crosslinking agent is preferably polyvalent, since this makes it easier to form a highly dimensional crosslinked structure and network, and increases the bulk cohesive strength of the resulting pressure-sensitive adhesive layer.

[0047] The pressure-sensitive adhesive contains a tackifier resin. When the pressure-sensitive adhesive contains the tackifier resin, the resulting pressure-sensitive adhesive layer has excellent adhesion to the adherend.

[0048] The softening temperature of the tackifier resin is preferably 90°C as a lower limit, and 180°C as an upper limit. When the softening temperature of the tackifier resin is 90°C or higher, the pressure-sensitive adhesive layer has better heat resistance and the creep resistance at high temperatures is further improved. When the softening temperature of the tackifier resin is 180°C or lower, the pressure-sensitive adhesive layer is more likely to be flexible and has better adhesion to rough surfaces. The softening temperature of the tackifier resin is more preferably 100°C as a lower limit, more preferably 110°C as a lower limit, and particularly preferably 120°C as a lower limit, and more preferably 170°C as an upper limit, and even more preferably 165°C as an upper limit. The "softening temperature" mentioned above means the softening temperature measured by the JIS K2207 ring and ball method.

[0049] The hydroxyl value of the tackifier resin is preferably 10 mgKOH / g at its lower limit, and 200 mgKOH / g at its upper limit. When the hydroxyl value of the tackifier resin is 10 mgKOH / g or more, the softening temperature of the tackifier resin is likely to be high. When the hydroxyl value of the tackifier resin is 200 mgKOH / g or less, the reactivity with the crosslinking agent is not too high, and it is possible to suppress the inhibition of crosslinking of the (meth)acrylic copolymer or the occurrence of a graft reaction with the (meth)acrylic copolymer. The hydroxyl value of the tackifier resin is more preferably 20 mgKOH / g at its lower limit, even more preferably 25 mgKOH / g at its lower limit, and particularly preferably 30 mgKOH / g at its upper limit, and more preferably 150 mgKOH / g at its upper limit, even more preferably 120 mgKOH / g at its upper limit, and particularly preferably 100 mgKOH / g at its upper limit. The "hydroxyl value" can be measured according to JIS K1557 (phthalic anhydride method).

[0050] Examples of the tackifier resin include rosin-based resins such as rosin ester-based resins, terpene-based resins such as terpene phenol resins, petroleum-based resins, etc. These tackifier resins may be used alone or in combination of two or more. Among these, rosin ester resins, terpene phenol resins, and combinations thereof are preferred, and terpene phenol resins are more preferred.

[0051] The terpene phenol resin is a resin obtained by polymerizing terpene in the presence of phenol. The terpene phenol resin has good compatibility with the (meth)acrylic copolymer, and is easily grafted with the (meth)acrylic copolymer, and is easily incorporated into the pressure-sensitive adhesive layer. As a result, the surface of the pressure-sensitive adhesive layer becomes polymer-rich and flexible, and can have higher adhesive strength to rough surfaces. Meanwhile, the grafting of the terpene phenol resin with the (meth)acrylic copolymer increases the bulk cohesive strength of the pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer has better creep resistance.

[0052] Examples of commercially available terpene resins include YS Polystar G150 (hydroxyl value 140 mg KOH / g, softening temperature 150° C.), YS Polystar T100 (hydroxyl value 60 mg KOH / g, softening temperature 100° C.), YS Polystar G125 (hydroxyl value 140 mg KOH / g, softening temperature 125° C.), YS Polystar T115 (hydroxyl value 60 mg KOH / g, softening temperature 115° C.), YS Polystar T130 (hydroxyl value 60 mg KOH / g, softening temperature 130° C.), and YS Polystar T160 (hydroxyl value 60 mg KOH / g, softening temperature 160° C.) (all manufactured by Yasuhara Chemical Co., Ltd.).

[0053] The rosin ester resin is a resin obtained by esterifying, with an alcohol, a rosin resin mainly composed of abietic acid, a disproportionated rosin resin, a hydrogenated rosin resin, a dimer (polymerized rosin resin) of a resin acid such as abietic acid, etc. A part of the hydroxyl group of the alcohol used for esterification is not used for esterification and is contained in the resin, so that the hydroxyl value is adjusted to the above-mentioned range. Examples of the alcohol include polyhydric alcohols such as ethylene glycol, glycerin, and pentaerythritol. In addition, a resin obtained by esterifying a rosin resin is a rosin ester resin, a resin obtained by esterifying a disproportionated rosin resin is a disproportionated rosin ester resin, a resin obtained by esterifying a hydrogenated rosin resin is a hydrogenated rosin ester resin, and a resin obtained by esterifying a polymerized rosin resin is a polymerized rosin ester resin.

[0054] Among the above disproportionated rosin ester resins, commercially available ones include, for example, Super Ester A75 (hydroxyl value 23 mg KOH / g, softening temperature 75° C.), Super Ester A100 (hydroxyl value 16 mg KOH / g, softening temperature 100° C.), Super Ester A115 (hydroxyl value 19 mg KOH / g, softening temperature 115° C.), and Super Ester A125 (hydroxyl value 15 mg KOH / g, softening temperature 125° C.) (all manufactured by Arakawa Chemical Industries, Ltd.). Examples of the hydrogenated rosin ester resin include Pine Crystal KE-359 (hydroxyl value 42 mg KOH / g, softening temperature 100° C.) and Ester Gum H (hydroxyl value 29 mg KOH / g, softening temperature 70° C.) (both manufactured by Arakawa Chemical Industries, Ltd.). Examples of the polymerized rosin ester resin include PENSEL D135 (hydroxyl value 45 mg KOH / g, softening temperature 135° C.), PENSEL D125 (hydroxyl value 34 mg KOH / g, softening temperature 125° C.), and PENSEL D160 (hydroxyl value 42 mg KOH / g, softening temperature 160° C.) (all manufactured by Arakawa Chemical Industries, Ltd.).

[0055] The content of the tackifier resin is preferably 10 parts by mass at the lower limit and 60 parts by mass at the upper limit relative to 100 parts by mass of the (meth)acrylic copolymer. By having the content of the tackifier resin within the above range, the pressure-sensitive adhesive layer has better interfacial adhesion and better retention performance. The more preferred lower limit of the content is 15 parts by mass, and even more preferred lower limit is 20 parts by mass, and the more preferred upper limit is 50 parts by mass, and even more preferred upper limit is 45 parts by mass.

[0056] The pressure-sensitive adhesive may contain additives such as solvents, plasticizers, emulsifiers, softeners, fillers, pigments, dyes, silane coupling agents, antioxidants, etc. In the pressure-sensitive adhesive tape of the present invention, the amount of the solvents that are the source of CO2 emitted in the manufacturing process can be reduced.

[0057] The pressure-sensitive adhesive preferably contains 0.03% by mass or more of a compound having a hydroxyl group in the solid content, and 2% by mass or more of a compound having a carboxyl group in the solid content. By containing 0.03% by mass or more of a compound having a hydroxyl group in the solid content, and 2% by mass or more of a compound having a carboxyl group in the solid content, the bulk cohesive force in the obtained pressure-sensitive adhesive layer becomes larger, and the pressure-sensitive adhesive layer becomes more excellent in heat resistance. The pressure-sensitive adhesive more preferably contains 0.05% by mass or more of the compound having a hydroxyl group. In addition, the pressure-sensitive adhesive more preferably contains 3% by mass or more of the compound having a carboxyl group. The compound having a hydroxyl group and the compound having a carboxyl group may be any component contained in the solid content of the pressure-sensitive adhesive. The above "solid content" refers to components excluding the solvent.

[0058] The preferred upper limit of the viscosity of the adhesive when applied is 10,000 mPa·s. By applying the adhesive with a viscosity of 10,000 mPa·s or less, it becomes easy to apply the adhesive smoothly without problems such as air bubbles or glue streaks. The more preferred upper limit of the viscosity of the adhesive when applied is 9,000 mPa·s, and the even more preferred upper limit is 8,000 mPa·s. Furthermore, the preferred lower limit of the viscosity when the adhesive is applied is 1500 mPa·s. By applying the adhesive with a viscosity of 1500 mPa·s or more, sufficient pressure can be obtained when extruding the adhesive, making it easy to apply the adhesive to the desired thickness and width. The more preferred lower limit of the viscosity when the adhesive is applied is 2000 mPa·s. The viscosity of the pressure-sensitive adhesive when it is applied can be measured using a Brookfield viscometer under conditions of 23° C. and 12 rpm.

[0059] The pressure-sensitive adhesive layer has a glass transition temperature of -10°C as a lower limit and a glass transition temperature of 30°C as a upper limit. When the pressure-sensitive adhesive layer has a glass transition temperature of -10°C or higher, the heat resistance and bulk cohesive force are high, resulting in superior retention performance and high-temperature repulsion resistance. When the pressure-sensitive adhesive layer has a glass transition temperature of 30°C or lower, the adhesive layer has superior adhesion to the interface. The pressure-sensitive adhesive layer has a more preferred lower limit of -5°C, an even more preferred lower limit of 0°C, an even more preferred lower limit of 5°C, a more preferred upper limit of 25°C, an even more preferred upper limit of 20°C, and an even more preferred upper limit of 15°C. In this specification, the "glass transition temperature" refers to the temperature at which a maximum due to micro-Brownian motion appears among the maximums of loss tangent (tan δ) obtained by dynamic viscoelasticity measurement. For the dynamic viscoelasticity measurement carried out in measuring the glass transition temperature and storage modulus of the pressure-sensitive adhesive layer described below, the following method can be used, for example. That is, first, the above-mentioned samples of the pressure-sensitive adhesive layer are stacked to prepare a laminate having a thickness of about 1 mm, and then cut into a 6 mm × 10 mm specimen. The specimen is subjected to dynamic viscoelasticity measurement in a shear mode under a nitrogen atmosphere at a measurement temperature of -40°C to 140°C, a heating rate of 5°C / min, a frequency of 10 Hz, and a strain of 0.08% using a dynamic viscoelasticity measuring device (IT Measurement and Control Co., Ltd., "DVA-200").

[0060] The preferred lower limit of the storage modulus G'(80°C) of the pressure-sensitive adhesive layer at 80°C is 1.0 × 10 4 The pressure-sensitive adhesive layer has a storage modulus G'(80°C) of 1.0 × 10 4 The pressure-sensitive adhesive layer has a larger bulk cohesive force at high temperatures, and thus has better creep resistance and high-temperature repulsion resistance at high temperatures. 4 Pa, and a more preferable lower limit is 2.0×10 4 Pa, and an even more preferable lower limit is 5.0×10 4 Pa, and the particularly preferred lower limit is 8.0×10 4 It is Pa. If the storage modulus G'(80°C) of the pressure-sensitive adhesive layer is too high, the storage modulus at room temperature also becomes high, and the adhesive strength to a rough surface decreases. Therefore, the preferred upper limit of the storage modulus G'(80°C) of the pressure-sensitive adhesive layer is 2.0 × 10 5 It is Pa.

[0061] The preferred lower limit of the thickness of the pressure-sensitive adhesive layer is 10 μm, and the preferred upper limit is 100 μm. When the thickness of the pressure-sensitive adhesive layer is 10 μm or more, the pressure-sensitive adhesive layer is more likely to bite into the adherend and has a higher peel resistance, resulting in better adhesion to rough surfaces. When the thickness is 100 μm or less, the pressure-sensitive adhesive layer is less likely to slip when a shear force is applied thereto, resulting in better retention performance. The more preferred lower limit of the thickness of the pressure-sensitive adhesive layer is 12 μm, and even more preferred lower limit is 15 μm, and the more preferred upper limit is 60 μm, and even more preferred upper limit is 50 μm.

[0062] The pressure-sensitive adhesive tape preferably has a substrate. The substrate is preferably a resin film. The resin film is preferably a polyester resin film or a polypropylene resin film. Among them, a polyester resin film is preferred because it is flat, has little thickness variation, and has high strength, and among the polyester resin films, a polyethylene terephthalate film is more preferred.

[0063] The above-mentioned base material may contain additives such as a filler, an ultraviolet absorber, a light stabilizer, and an antistatic agent, within the range that does not impair the physical properties of the base material.

[0064] The thickness of the substrate is appropriately selected according to the application, but the preferred lower limit is 5 μm, and the preferred upper limit is 200 μm. The substrate having a thickness of 200 μm or less is suitable for use in fixing electronic components, and can reduce CO2 emissions during production. The more preferred lower limit of the thickness of the substrate is 10 μm, and even more preferred lower limit is 15 μm, and the more preferred upper limit is 100 μm, and even more preferred upper limit is 50 μm.

[0065] The pressure-sensitive adhesive tape of the present invention may have the pressure-sensitive adhesive layer on only one side of the substrate, or may have the pressure-sensitive adhesive layer on both sides of the substrate. Among these, it is preferable that the pressure-sensitive adhesive layer is on both sides of the substrate.

[0066] The method for producing the pressure-sensitive adhesive tape of the present invention is not particularly limited. For example, when the pressure-sensitive adhesive layer has the same composition and thickness on both sides of the substrate, the following method can be mentioned. First, a pressure-sensitive adhesive is prepared that contains a (meth)acrylic copolymer, a crosslinking agent, a tackifier resin, and a solvent and other components that are used as necessary. Next, the pressure-sensitive adhesive obtained above is applied to the release-treated surface of a release film, one side of which has been release-treated, and then dried to prepare a laminated sheet having a pressure-sensitive adhesive layer on the release-treated surface of the release film. A total of two laminated sheets are prepared in the same manner. Next, the pressure-sensitive adhesive layers of the two laminated sheets are transferred to a substrate and laminated together to obtain a pressure-sensitive adhesive sheet having pressure-sensitive adhesive layers on both sides of the substrate.

[0067] From the viewpoint of enhancing both the holding performance and adhesiveness of the pressure-sensitive adhesive tape of the present invention, it is preferable that the pressure-sensitive adhesive tape of the present invention has excellent high-temperature repulsion resistance. The high-temperature repulsion resistance can be evaluated, for example, by the following method. Figure 2 shows a schematic diagram illustrating the method of testing high-temperature repulsion resistance. That is, the adhesive tape 1 of the present invention is cut into a strip of 25 mm width x 300 mm length, and the adhesive layer on the side not being measured is laminated to a PET film 4 (thickness 100 μm, width 25 mm, length 300 mm). Next, the adhesive layer on the side being measured is laminated to a SUS plate 2 (a SUS304 plate washed with ethanol and then wiped dry) so that the short side of the adhesive tape 1 overlaps one side of the SUS plate, and then a 2 kg rubber roller is moved back and forth at a speed of 300 mm / min 5 times to press the adhesive tape 1, and then the adhesive tape is left to stand at 23 ° C for 72 hours to prepare a test piece. The prepared test piece is further heated in an oven at 80 ° C for 15 minutes, and then a high temperature repulsion resistance test is performed in which a load of 100 g is applied to the test piece placed horizontally under the condition of 80 ° C so that the load is perpendicular to the test piece and the state is maintained for 144 hours. If the entire adhesive tape falls, the time when a load of 100 g was applied is set as 0 hour and the drop time is measured, and if the entire adhesive tape does not fall, the peel length of the adhesive tape (the length between the double-headed arrows in Figure 2) is visually measured. If the result of the high-temperature repulsion resistance test shows that the entire adhesive tape does not fall and the peel length is 60 mm or less, the adhesive tape of the present invention has excellent high-temperature repulsion resistance. Effect of the Invention

[0068] According to the present invention, it is possible to provide a pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer that is excellent in holding performance and adhesiveness while using a (meth)acrylic copolymer having a low molecular weight. [Brief description of the drawings]

[0069] [Figure 1] FIG. 1 is a schematic diagram showing a method for a retention test. [Diagram 2] FIG. 2 is a schematic diagram showing a method for testing high-temperature repulsion resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0070] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0071] (Preparation of Acrylic Copolymers A to S) A solvent shown in Table 1 was added to a reactor equipped with a thermometer, a stirrer, and a cooling tube, and the inside of the reactor was replaced with nitrogen. The reactor was then heated to start reflux. After the solvent boiled, a polymerization initiator 1 shown in Table 1 was added, and a mixed solution of a monomer and a chain transfer agent shown in Table 1 was dropped into the reactor from a dropping funnel over a period of 2 hours. Then, a polymerization initiator 2 shown in Table 1 was further added, and the time when the dropping started was set as the polymerization start time. The polymerization reaction was carried out for a total of 6 hours from the start of polymerization, and a solution containing acrylic copolymers A to S was obtained. The materials in Table 1 are as follows: BA: Butyl acrylate 2EHA: 2-Ethylhexyl acrylate C7: n-heptyl acrylate HEA: Hydroxyethyl acrylate Aac: acrylic acid AIBN: 2,2'-azobis(isobutyronitrile)

[0072] [Table 1]

[0073] (Examples 1 to 23, Comparative Examples 1 to 8) (1) Preparation of adhesive To the obtained solution containing acrylic copolymers A to S, the materials were added in the compositions shown in Tables 2 and 3, and the mixture was stirred to obtain a pressure-sensitive adhesive. The content of the compound having a hydroxyl group in the solid content and the content of the compound having a carboxyl group in the solid content of the obtained pressure-sensitive adhesive are shown in Tables 2 and 3. The materials in Tables 2 and 3 are as follows: Coronate L45: Isocyanate-based crosslinking agent (manufactured by Tosoh Corporation) KE388: Hydrogenated rosin ester resin (manufactured by Arakawa Chemical Industries, hydroxyl value 45 mgKOH / g, softening temperature 150°C) KE359: Hydrogenated rosin ester resin (manufactured by Arakawa Chemical Industries, hydroxyl value 40 mg KOH / g, softening temperature 100°C) D135: Polymerized rosin ester resin (Arakawa Chemical Industries, hydroxyl value 40 mgKOH / g, softening temperature 135°C) G150: Terpene resin (manufactured by Yasuhara Chemical Co., Ltd., hydroxyl value 100 mg KOH / g, softening temperature 150°C)

[0074] (2) Preparation of adhesive tape A polyethylene terephthalate film with one side treated for release was prepared. The adhesive obtained in "(1) Preparation of adhesive" above was applied to the release-treated surface of this polyethylene terephthalate film and dried at 110°C for 5 minutes to promote crosslinking of the (meth)acrylic copolymer in the adhesive, producing a laminate sheet having an adhesive layer on the release-treated surface of the polyethylene terephthalate film. Another laminate sheet was produced in the same manner, yielding a total of two of the above laminate sheets. Next, a polyethylene terephthalate film (thickness 25 μm) was prepared as a substrate. One of the laminated sheets was laminated on one surface of this substrate from the adhesive layer side, and the adhesive layer was transferred to the substrate and laminated together. The other laminated sheet was laminated on the other surface of the substrate from the adhesive layer side, and the adhesive layer was transferred to the substrate and laminated together. This resulted in a double-sided adhesive tape in which adhesive layers having thicknesses shown in Tables 2 and 3 were provided on both sides of the substrate.

[0075] (Weight average molecular weight (Mw copolymer), peak top molecular weight (Mp copolymer), and polydispersity (Mw copolymer / Mn copolymer) of (meth)acrylic copolymer obtained by alkaline decomposition) 300 mg of the adhesive layer was collected from the obtained double-sided adhesive tape. The collected adhesive layer, 6 mL of ethanol, and 7 mL of a 60% KOH aqueous solution were added to a pressure vessel, and pressure hydrolysis was performed in an oven at 160° C. for 60 hours to alkali-decompose the crosslinking points of the crosslinked product in the adhesive layer, thereby obtaining a (meth)acrylic copolymer. The (meth)acrylic copolymer obtained was analyzed by gel permeation chromatography (GPC) (Waters, "2690 Separations Model") to measure the molecular weight distribution in terms of polystyrene. The weight average molecular weight (Mw copolymer), peak top molecular weight (Mp copolymer), and polydispersity (Mw copolymer / Mn copolymer) of the (meth)acrylic copolymer obtained by alkali decomposition, derived from the molecular weight distribution obtained, are shown in Tables 2 and 3. The GPC was performed under the following conditions. Eluent: tetrahydrofuran (THF) Flow rate: 0.4mL / min Detector: RI differential refractometer Column: LF-804 (Shoko) Column temperature (measurement temperature): 40℃ Injection volume: 20μL

[0076] (Weight average molecular weight of sol component (Mw sol) and Mw sol-Mw copolymer) The adhesive layer of the obtained double-sided adhesive tape was immersed in tetrahydrofuran (THF) at 23° C. for 24 hours, and the insoluble matter was removed by filtration through a 200-mesh wire screen to obtain a sol component of the adhesive layer. The sol component of the obtained pressure-sensitive adhesive layer was analyzed by gel permeation chromatography (GPC) (Waters, "2690 Separations Model") to measure the molecular weight distribution in terms of polystyrene. The weight average molecular weight of the sol component (Mw sol) derived from the obtained molecular weight distribution, and the value obtained by subtracting the weight average molecular weight of the (meth)acrylic copolymer obtained by alkaline decomposition from the weight average molecular weight of the sol component (Mw sol-Mw copolymer) are shown in Tables 2 and 3. The above GPC was performed under the following conditions. Eluent: tetrahydrofuran (THF) Flow rate: 0.4mL / min Detector: RI differential refractometer Column: LF-804 (Shoko) Column temperature (measurement temperature): 40℃ Injection volume: 20μL

[0077] (Gel fraction of adhesive layer) The adhesive layer of the obtained double-sided adhesive tape was sampled as W1 (g), and the sampled adhesive layer was immersed in ethyl acetate at 23°C for 24 hours, and the insoluble matter was filtered through a 200-mesh wire net. The residue on the wire net was dried by heating at 110°C, and the mass W2 (g) of the obtained dry residue was measured. The gel fraction (degree of crosslinking) was calculated from the obtained W1 and W2 according to the following formula (I). The obtained gel fractions are shown in Tables 2 and 3. Gel fraction (mass%) = 100 × W2 / W1(I)

[0078] (Storage modulus G'(80℃) and glass transition temperature of adhesive layer) The adhesive layers of the obtained double-sided adhesive tape were overlapped to prepare a laminate with a thickness of about 1 mm, and cut into 6 mm x 10 mm to obtain a test piece. The obtained test piece was subjected to dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (IT Measurement and Control Co., Ltd., "DVA-200") in a shear mode under a nitrogen atmosphere at a measurement temperature of -40°C to 140°C, a heating rate of 5°C / min, a frequency of 10Hz, and a strain of 0.08%, to obtain the storage modulus G' (80°C) at 80°C. In addition, the temperature at which the maximum due to micro-Brownian motion appeared among the maximums of the loss tangent (tanδ) obtained by the dynamic viscoelasticity measurement was taken as the glass transition temperature. The obtained storage modulus G' (80°C) and glass transition temperature are shown in Tables 2 and 3.

[0079] [Table 2]

[0080] [Table 3]

[0081] <Evaluation> The pressure-sensitive adhesives and double-sided pressure-sensitive adhesive tapes obtained in the Examples and Comparative Examples were evaluated as follows. The results are shown in Tables 4 and 5.

[0082] (processability) The solid content of the obtained adhesive was adjusted to 60% by mass, and the viscosity was measured at 23°C and 12 rpm using a B-type viscometer (manufactured by Eiko Seiki Co., Ltd., "RVDV-2+PRO") and spindle S04. The viscosity of the adhesive with the solid content adjusted to 70% by mass was also measured in the same manner. The processability was evaluated as follows: if the viscosity was 10,000 mPa·s or less, it was given an "O" rating; if it exceeded 10,000 mPa·s, it was given an "X" rating.

[0083] (retention performance) The obtained double-sided adhesive tape was cut into strips of 25 mm width, and then bonded to a SUS plate (SUS304 plate washed with ethanol and then wiped dry) by moving a 2 kg rubber roller back and forth at a speed of 300 mm / min. Next, a cut was made in the adhesive tape so that the adhesive area was 25 mm x 25 mm. After that, it was left to stand at 23 ° C for 20 minutes, placed in an oven at 80 ° C, heated for another 15 minutes, and then, while maintaining at 80 ° C, a load of 1 kg was applied in the shear direction using a 1 kg weight 3 as shown in Figure 1. It was confirmed whether the adhesive tape had fallen off, and if it had not fallen off after 24 hours, the amount of movement (displacement) from the cut position was measured with a scale magnifying glass. The holding performance was evaluated as follows: if the adhesive tape did not fall off and the slippage was 1 mm or less, it was marked "O"; if the adhesive tape did not fall off and the slippage was more than 1 mm, it was marked "△"; if the adhesive tape fell off, it was marked "X".

[0084] (Adhesiveness) The adhesive tape was cut into strips of 25 mm width, and then attached to a SUS plate (SUS304 plate washed with ethanol and then wiped dry) by rolling a 2 kg rubber roller back and forth at a speed of 300 mm / min. The tape was then left to stand for 20 minutes at a temperature of 23°C and a relative humidity of 50% to obtain a test piece. The obtained test piece was subjected to a tensile test using a tensile tester (manufactured by A&D, "RTI-1310") in accordance with JIS Z0237 at 23°C, a peel speed of 300 mm / min, and a peel angle of 180°, to measure the 180° peel adhesion. The adhesion was evaluated as follows: if the obtained 180° peel adhesion was 18 N / 25 mm or more, it was marked "○", if it was 15 N / 25 mm or more and less than 18 N / 25 mm, it was marked "△", and if it was less than 15 N / 25 mm, it was marked "×". In addition, instead of the SUS plate (SUS304 plate washed with ethanol and then wiped dry), a rough SUS plate was used and the 180° peel adhesive strength was measured in the same manner. The rough SUS plate was a SUS304 plate that had been washed with ethanol, then wiped dry and then polished with abrasive paper of grain size 80. The surface of the rough SUS plate was observed with a laser microscope and found to have an Ra of 1.7 μm and an Rz of 10 μm.

[0085] [Table 4]

[0086] [Table 5] [Industrial Applicability]

[0087] According to the present invention, it is possible to provide a pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer that is excellent in holding performance and adhesiveness while using a (meth)acrylic copolymer having a low molecular weight. [Explanation of symbols]

[0088] 1 adhesive tape 2 SUS board 3. 1kg load (weight) 4. PET film 5. 100g load (weight)

Claims

1. An adhesive tape having an adhesive layer, the pressure-sensitive adhesive layer contains a crosslinked product of a pressure-sensitive adhesive comprising a (meth)acrylic copolymer, a crosslinking agent, and a tackifier resin, a (meth)acrylic copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product is subjected to GPC measurement using RI detection with a differential refractometer, the (meth)acrylic copolymer has a weight average molecular weight of 80,000 or more and less than 500,000 in a molecular weight range of 5,000 or more; The adhesive tape adhered to a stainless steel plate is subjected to a retention test in which a load of 1 kg is applied in a shear direction at 80° C. for 24 hours, and the adhesive tape does not fall off. The adhesive tape has a 180° peel strength of 15 N / 25 mm or more against a SUS plate. An adhesive tape characterized by:

2. An adhesive tape having an adhesive layer, the pressure-sensitive adhesive layer contains a crosslinked product of a pressure-sensitive adhesive comprising a (meth)acrylic copolymer, a crosslinking agent, and a tackifier resin, When a (meth)acrylic copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product is subjected to GPC measurement using RI detection with a differential refractometer, the (meth)acrylic copolymer has a weight average molecular weight of 80,000 or more and less than 500,000 in a molecular weight range of 5,000 or more; and The following first configuration, the following second configuration, or the following third configuration is satisfied. An adhesive tape characterized by: First configuration: the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the pressure-sensitive adhesive layer is 5% by mass or more. Second configuration: the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, the gel fraction of the pressure-sensitive adhesive layer is less than 5 mass%, and when a sol component of the pressure-sensitive adhesive layer is subjected to GPC measurement by RI detection with a differential refractometer, the weight average molecular weight of the sol component in a molecular weight range of 5000 or more is subtracted from the weight average molecular weight of the (meth)acrylic copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product in a GPC measurement by RI detection with a differential refractometer, the weight average molecular weight of the (meth)acrylic copolymer in a molecular weight range of 5000 or more is 80,000 or more. Third configuration: the pressure-sensitive adhesive contains 0.1 parts by mass or more and less than 6 parts by mass of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the pressure-sensitive adhesive layer exceeds 30% by mass.

3. The pressure-sensitive adhesive tape according to claim 2 , which satisfies the first configuration.

4. The adhesive tape according to claim 2 , which satisfies the second configuration.

5. The pressure-sensitive adhesive tape according to claim 2 , which satisfies the third characteristic.

6. The pressure-sensitive adhesive layer satisfies the following first configuration, the following second configuration, or the following third configuration: The adhesive tape according to claim 1. First configuration: the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the pressure-sensitive adhesive layer is 5% by mass or more. Second configuration: the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, the gel fraction of the pressure-sensitive adhesive layer is less than 5 mass%, and when a sol component of the pressure-sensitive adhesive layer is subjected to GPC measurement by RI detection with a differential refractometer, the weight average molecular weight of the sol component in a molecular weight range of 5000 or more is subtracted from the weight average molecular weight of the (meth)acrylic copolymer obtained by alkali decomposition of the crosslinking points of the crosslinked product in a GPC measurement by RI detection with a differential refractometer, the weight average molecular weight of the (meth)acrylic copolymer in a molecular weight range of 5000 or more is 80,000 or more. Third configuration: the pressure-sensitive adhesive contains 0.1 parts by mass or more and less than 6 parts by mass of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the gel fraction of the pressure-sensitive adhesive layer exceeds 30% by mass.

7. The pressure-sensitive adhesive layer has a first configuration in which the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the pressure-sensitive adhesive layer has a gel fraction of 5% by mass or more and less than 30% by mass, or As the third configuration, the pressure-sensitive adhesive contains 1.5 parts by mass or more and less than 6 parts by mass of the crosslinking agent relative to 100 parts by mass of the (meth)acrylic copolymer, and the pressure-sensitive adhesive layer has a gel fraction of more than 30% by mass. The adhesive tape according to claim 2 or 6.

8. 8. The pressure-sensitive adhesive tape according to claim 7, wherein the pressure-sensitive adhesive layer has, as the first configuration, a configuration in which the pressure-sensitive adhesive contains 6 parts by mass or more of the crosslinking agent per 100 parts by mass of the (meth)acrylic copolymer, and the pressure-sensitive adhesive layer has a gel fraction of 5 mass% or more and less than 30 mass%.

9. The pressure-sensitive adhesive layer has, as the third configuration, a configuration in which the pressure-sensitive adhesive contains 1.5 parts by mass or more and less than 6 parts by mass of the crosslinking agent per 100 parts by mass of the (meth)acrylic copolymer, and the pressure-sensitive adhesive layer has a gel fraction of more than 30 mass%.

10. 10. The pressure-sensitive adhesive tape according to claim 1, wherein the weight average molecular weight of the sol component in the pressure-sensitive adhesive layer in a molecular weight range of 5,000 or more is 50,000 or more and 500,000 or less when the sol component is subjected to GPC measurement using RI detection with a differential refractometer.

11. The pressure-sensitive adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, wherein, when a (meth)acrylic copolymer obtained by alkaline decomposition of the crosslinking points of the crosslinked product is subjected to GPC measurement using RI detection with a differential refractometer, the (meth)acrylic copolymer has a peak top molecular weight of 70,000 or more and 300,000 or less in a molecular weight range of 5,000 or more.

12. 12. The adhesive tape according to claim 1, wherein the adhesive contains a compound having a hydroxyl group in an amount of 0.03% by mass or more based on the solid content, and a compound having a carboxyl group in an amount of 2% by mass or more based on the solid content.

13. 13. The pressure-sensitive adhesive tape according to claim 1, wherein the (meth)acrylic copolymer contains 50% by mass or more of structural units derived from a monomer having an alkyl group having 6 or more carbon atoms.

14. The pressure-sensitive adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13, wherein the pressure-sensitive adhesive layer has a glass transition temperature of -10°C or higher and 30°C or lower.

15. The pressure-sensitive adhesive layer has a storage modulus G'(80°C) of 1.0 x 10 4 The pressure-sensitive adhesive tape according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14, having a modulus of elasticity of 1 Pa or more.

16. 16. The adhesive tape according to claim 1, wherein the adhesive layer has a thickness of 10 μm or more and 100 μm or less.

17. 17. The adhesive tape according to claim 1, wherein the adhesive tape has a substrate, the substrate being a polyester resin film or a polypropylene resin film, and the substrate has a thickness of 5 μm or more and 200 μm or less.

18. The adhesive tape according to claim 1 , wherein the adhesive tape has a substrate and the adhesive layer is provided on both sides of the substrate.

Citation Information

Patent Citations

  • Water dispersion type acrylic adhesive composition and adhesive tape

    JP2010248465A

  • Adhesive composition and adhesive sheet

    JP2018177902A

  • Repeelable adhesive composition and adhesive tape

    JP2021020986A

  • Double-sided adhesive tape for portable electronic device

    WO2016035747A1

  • (METH)acrylic copolymer and manufacturing method of same, adhesive composition and adhesive sheet

    WO2018025807A1